Studi hubungan antara penguasaan kosakata dan sikap percaya diri dengan keterampilan berbicara peserta didik kelas V sekolah dasar - Kirana, GC; Slamet, St. Y; Budiharto, Tri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The purpose of this research was (1) vocabulary mastery wuth speaking skills, (2)selft-confidentÂ  with speaking skill, (3) vocabulary mastery and self-confident with the speaking skills elementary school at grade 5TH Ahmad Yani Cluster, Cilacap Selatan District, CilacapCity. This study uses a quantitative correlation reaearch ,ethod. Sampling using clusterrandom sampling with a populationÂ  elemtary school at grade 5TH students Ahmad YaniCluster. The data analysis techniques used simple correlastion analysis and multiplecorrelastion assisted by Ms.Excel. The result of the simple correlation analysis indicate thatthe hypothesis states that there is a significant and positive reliationship between vocabularymastery with speaking skilss. Based on the data analysis, it can be conclude of vocabularymastery and speaking skills r(0.798), the coefficient of the correlation was tested with the ttest, the result tcount (11.011)> ty1 (1.995) showing a significant correlation between the self confident and speaking skils ry2 table (0.9129), the coefficient of the correlation was tested with the ttest, the rusult tcount (18.580)> t (1.995) showing a significant correlation between both the vocabulary mastery and self-confident together with speaking skills rtable (0.856). the coefficient the F test obtained Fcount = 92.907real level Î± = 0.05, with df = 68 obtained Fy12 = 3.131, then Fcount > Ftable